Numerical Simulation of Underwater Propeller Noise - M.R., Bagheri; M.S., Seif; H., Mehdigholi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Noise reduction and control is an important problem in the performance of underwater acoustic systems and in the habitability of the passenger ship for crew and passenger. Furthermore, sound generated by a propeller is critical in underwater detection and it is often related to the survivability of the vessel. This paper presents a numerical study on noises of the underwater propeller for different performance conditions. The non-cavitating and blade sheet cavitation noise generated by an underwater propeller is analyzed numerically in this study. The flow field is analyzed with finite volume method (FVM), and then the time-dependent flow field data are used as the input for Ffowcs Williams–Hawkings (FW-H) formulation to predict the far-field acoustics. Noise characteristics are presented according to noise sources and conditions. The developed flow solver is applied to the model propeller in uniform inflow. Computed results are shown to be in good agreement with other numerical results. The overall results suggest that the present approach is a practicable tool for predicting cavitation and non-cavitation noise of propellers in far field.